Digital Marketing Content, Value Co-Creation, and Product Branding on Perceived Product Exclusivity in Batik Industry - Muchlison, Sonny; Sugiono, Edi; Lestari, Rahayu (Digital Innovation : International Journal of Management, 2025)
This study explores the relationships between digital marketing content, value co-creation, and product branding on perceived product exclusivity within the Indonesian batik industry. As traditional industries face increasing pressure to modernize while preserving cultural heritage, understanding these marketing dynamics is crucial for achieving a sustainable competitive advantage. The study employed a quantitative methodology with saturated sampling, analyzing data from 92 batik enterprises using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The measurement model demonstrated strong reliability and validity, with all constructs meeting the established criteria for internal consistency and discriminant validity. Structural model results revealed that all three marketing variables significantly influence perceived product exclusivity. Among these variables, product branding showed the strongest effect (β = 0.358, p < 0.001), followed by digital marketing content (β = 0.312, p < 0.001) and value co-creation (β = 0.276, p < 0.001). This indicates that the branding strategies implemented by batik enterprises play a pivotal role in shaping consumers' perceptions of exclusivity. The integrated model explained 61.5% of the variance in perceived product exclusivity (R² = 0.615), with strong predictive relevance (Q² = 0.438). These findings underscore the importance of developing a strategic brand that not only reflects the unique qualities of batik but also resonates with contemporary consumer expectations. Additionally, the study highlights the role of digital marketing content in strengthening these perceptions and the significance of facilitating customer co-creation to enhance engagement and exclusivity. In conclusion, batik enterprises are encouraged to prioritize brand development while implementing comprehensive digital marketing strategies and fostering customer involvement in co-creation activities. This approach will enhance the exclusivity of their products and improve their market positioning within the contemporary cultural products landscape.